Go Web Development Cookbook : Build full-stack web applications with Go. - Aggarwal, Arpit (Packt Publishing, 2018)
Go is an open source programming language that is designed to scale and support concurrency at the language level. This gives you the liberty to write large concurrent web applications with ease. From creating web application to deploying them on Amazon Cloud Services, this book will be your one-stop guide to learn web development in Go.